2005
DOI: 10.1590/s0104-66322005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic ammonium oxidation in a bioreactor treating slaughterhouse wastewater

Abstract: -Ammonium oxidation was thought to be an exclusively aerobic process; however, as recently described in the literature, it is also possible under anaerobic conditions and this process was named ANAMMOX. This work describes the operation of a system consisting of a denitrifying reactor coupled to a nitrifying reactor used for removal of nitrogen from slaughterhouse wastewater. During operation of the denitrifying reactor an average nitrogen ammonium removal rate of 50 mg/Ld was observed. This biomass was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Partial nitritation systems were developed by the Delft University of Technology in 1996-1999 [11] and have several advantages over total nitritation-based technologies, such as 25% savings in aeration, 30% reduction of biomass generation, with a biomass yield of about 0.15 g biomass (g NH 4 + -N) −1 [12], and 20% less CO 2 emission [11]. Partial nitritation bioreactors at the laboratory scale have been reported to successfully treat food processing and agriculture industry wastewater, reject wastewater and slaughterhouse wastewater or swine manure wastewater, among others [13][14][15][16][17][18][19]. Within a partial nitritation reactor, the main performance is the oxidation of ammonium to nitrite, and therefore, there is an accumulation of nitrite in the system.…”
Section: -80mentioning
confidence: 99%
“…Partial nitritation systems were developed by the Delft University of Technology in 1996-1999 [11] and have several advantages over total nitritation-based technologies, such as 25% savings in aeration, 30% reduction of biomass generation, with a biomass yield of about 0.15 g biomass (g NH 4 + -N) −1 [12], and 20% less CO 2 emission [11]. Partial nitritation bioreactors at the laboratory scale have been reported to successfully treat food processing and agriculture industry wastewater, reject wastewater and slaughterhouse wastewater or swine manure wastewater, among others [13][14][15][16][17][18][19]. Within a partial nitritation reactor, the main performance is the oxidation of ammonium to nitrite, and therefore, there is an accumulation of nitrite in the system.…”
Section: -80mentioning
confidence: 99%
“…During the start-up of the reactors, the nitrite was present in low concentration in seeds, but further nitrite concentration was produced due to the activity of nitrifiers evolved with the initial dissolved oxygen present in the reactors. The anammox biomass was developed by using this nitrite as electron acceptor (Reginatto et al 2005). The concentration of nitrate in the reactors demonstrated that nitrate was probably evolved from nitrite to generate reducing equivalents for carbon dioxide fixation and it showed the growth of biomass (Van de Graaf et al 1996).…”
Section: Anammox Enrichment In 100-ml Reactorsmentioning
confidence: 99%
“…Reginatto et al (2005) desenvolveram um trabalho descrevendo a capacidade da biomassa de um reator de nitrificação-desnitrificação em tratar águas residuárias de esgoto doméstico para a remoção de nitrogênio pelo processo ANAMMOX. Araújo et al (2010) também demonstraram enriquecimento de bactérias com atividade ANAMMOX a partir de lodo proveniente de esgoto doméstico de Belo Horizonte, MG, e reportaram a predominância de Candidatus Brocardia anammoxidans, após 6 meses de adaptação, utilizando alimentação sintética com concentrações de nitrogênio aplicadas menores que 180 mg L -1 (até 95 mg N-NO 2 -e até 82 mg N-NH 4 + ).…”
Section: Anammox No Brasilunclassified